D 6.1 Interim biocomposite evaluation review - Pinto, A. (2013)
This deliverable is a review report which evaluates the progress and feasibility of the biocomposite systems, designs and installations, taking into account the information resulting from the work developed in the aim of Biobuild project. The main steps followed in the project up to this moment to develop bio-systems with such characteristics can be summarized as follows: · Use of additives and modifications to create durable natural fibres. · Use of additives and modifications to create durable bio-based resins. · Combine the improved resin and fibres to create durable and strong biocomposites. · Combine the improved natural fibres, resins and core materials to make composite components having mechanical properties, durability and functionality suitable for the selected construction applications. · Produce panels, profiles and sandwich structures for the selected construction applications. In terms of baseline resin/fibre properties, it was concluded that for both fibre reinforced composites (flax and jute fibre reinforced UP and epoxy composites) the increased moisture absorption is accompanied by a decrease in longitudinal stiffness and strength and by an increased plasticity, leading to an increase in longitudinal strain-to-failure. In general, the longitudinal stiffness of flax fibre composites decreases to 1/2 of its initial value, whereas that of jute fibre composites only goes down to 1/3 of its initial stiffness. On the other hand, the longitudinal strength of jute fibre composites is decreased by 1/4 after immersion, while that of flax fibre composites is only decreased by 15 %. Finally, for both fibre composites, the longitudinal strain-to-failure is increased by around 50 %. After the completion of the flax preforms benchmarking, these observations were made: · No significant difference between the different UD preforms tested in longitudinal direction. · The higher value of the transverse tensile strength for the Procotex UD is mainly due to the binding yarns. · Jute preform, as shown in the previous section, has lower property values than flax, but will still be relevant for low cost and non-structural parts. The same conclusion applies for the mat preform. · Tensile testing is defect sensitive which may explain the variations in results. Concerning the effect that fibre treatments have on the durability and moisture resistance, it was concluded that: · Quality of the samples makes difficult (impossible) to measure the effect of fibre treatment on the properties of the composite boards. · Water uptake is the main technical drawback for biocomposites. · Sealed edges and coating are other possibilities to improve the properties. · Jute is more water resistant; further examination is required for composites used in outdoor conditions. · None of the fibre treatments has a clear positive effect on the properties (water uptake nor strength) of the composite boards. · Research on fibre treatment within the project is needed for fundamental understanding and examining the possibilities for the future. The ongoing work in WP3 consists essentially in refining the processability of the various sandwich configurations in order to optimize the process parameters (time, temperature, pressure, degasification cycles, etc.) and to minimize rejections and wasted material (either BioBuild Project Deliverable Report 9 CONFIDENTIAL from a failed production cycle or from corrections in final dimensions) with the target of obtaining panels that are fit for the tasks they are intended for. Currently, the work on this task is far from finished, since on one hand problems regarding medium scale production are yet to be solved and on the other hand this is a task which should follow the development of the products, especially if, in the testing phase (including the Single Burning Item test and other equally important tests), it is found that any of those sandwich panel configurations need to be adjusted in order to comply with the target technical requirements. The main conclusion drawn from the processing of furan resin and glass fibres can be summarised as follows: · Furan resins have a very low reactivity (which can be increased) which means that pultrusion speed should be very low, making the process not economically viable from an industrial point of view. · The acid catalyst required to cure the resins and the high processing temperature required for the production induces fibre degradation and corrosion of steel parts in the production equipment. The action of acids can cause hydrolysis in cellulose chains and other binding materials, thereby degrading the fibre bundle mechanical properties. · It was therefore evident that this furan resin was unsuitable for use with natural fibres due to the acidic catalyst used to cure it. From the processing point of view, the first results of bio-polyester resins in combination with flax fibres can be summarized as follows: · The processing conditions for bio polyester resin are very similar to that of traditional resins, therefore similar pultrusion speed and heating temperature are used and similar resin stability are obtained. · The main drawbacks arise from the natural fibres. Dry natural fibres, when compared to glass fibre show fibre buckling, fibre rupture and fibre blockage near and in the mould. · In order to solve these issues, zinc stearate was added to the formulation and better results were obtained. More tests are underway to determine the proper additive concentration. · In principle this seems to be the best option in order to manufacture pultruded profiles with natural fibres and bio-resins. The main conclusions drawn from mechanical testing are summarized below: · Furan resins contains different amounts of water which, in conjunction with the water produced during the curing reaction, leads to pultruded profile with high void content and consequently poor mechanical properties. · In general low viscosity furan resins contain more water and lead to more porous composite materials with lower mechanical performance. · Furan resins with lower water content have higher viscosities, which prevent a good impregnation of reinforcing fibres and consequently produce pultruded panels with poor mechanical properties. · The third option is to select furan resins with higher reactivity, but even if this will have a positive effect on pultrusion speed (higher) it would decrease pot life and make it very difficult to work with. Obviously, lower reactivity leads to lower pultrusion speed and longer pot life but from an industrial point of view the process seems not to be economically viable. The BioBuild project entails the design and construction of four case studies, namely: an External Wall Panel (EWP), an External Cladding Kit (EKC), an Internal Partition Kit (IPK) BioBuild Project Deliverable Report 10 CONFIDENTIAL and a Suspended Ceiling Kit (SCK). All systems have been assessed on specific criteria, including fire-safety; dimensional stability; in-service resistance to loads; thermal and acoustic insulation; energy efficiency; and sustainability. The assessment of their performance is the aim of WP6. Aiming to evaluate the mechanical properties of each composite, the tensile and flexural properties of the composites were assessed according to the previously defined test plan; however, some modifications were made to the plan due to the insufficient amount of material that was made available to LNEC in respect to what was requested. All tests were performed at ambient temperature, except in case of the heat deflection temperature (HDT) test. From the results obtained it is possible to conclude the following: · The compression-moulded flax/furan sample shows the best performance and higher mechanical strength, when compared with the other samples tested (lamella sandwich of UP and 0/90º jute fabric on surfaces and cork in the core, and flax/furan on surfaces and thick cork prepreg in the core). · The composite constituted by flax/furan on surfaces and thick cork prepreg in the core, which is designed from sample 3 but adding cork to the core, shows delamination, even before testing. Thus, techniques to modify the surface/interface/interphase should be improved, in order to assure a performance similar or better than the composite without the inner cork layer. Additional work is still being done for a better performance evaluation of the referred composites. More samples are also needed in order to have a complete picture of the mechanical properties of all composites. So far, the initial ignitability tests on the basic performance of the materials showed that: · Furan resin does not ignite easily. · Furan/flax prepregs may ignite and sustain a slow propagation of combustion. · Flax (non-woven) mat is easily ignited and flame spreads very rapidly with total combustion being the final result. · Degradation of the furan surface (cracking, delamination, blistering) exposes the natural fibre reinforcement that will sustain combustion. · On the contrary, Biopol resins ignite (flame edge attack) and sustain the development and propagation of flame resulting in the total combustion of the material. · As expected, if agglomerated cork layers are exposed to flame attack they will ignite (easily if thickness is small) and sustain combustion. · Edges must be protected (in the end product/kit). Practical/cost effective solutions must be studied. · So far, only a RtF class E is “guaranteed” for most of the different component/material solutions assessed.